Evaluación de la aplicación de la metodología Lean construction en la planificación de un proyecto de infraestructura - Arroyo Orozco, Jorge José (2024)
The research focused on evaluating the application of the Lean Construction methodology in the planning of an infrastructure project, comparing it with the traditional critical path method. The main objective was to analyze the costs and times in the planning of a health infrastructure project, seeking improvements in efficiency and results. The results of the application of the Lean Construction methodology in a sanitary sewer project demonstrated a significant savings of $167,463.82, which represents a reduction of 3.28% in the planned bid budget based on the critical path method. It was also possible to increase indirect costs from 19% to 24% since the profit increased by 5%, which resulted in an improved final cost of 8.28%. This savings is notable in projects of this nature. In terms of time, the methodology helped maintain precise control over the progress of the project, evidenced by the accumulated executed progress curve, which remained above the programmed curve, demonstrating that there were no delays in the project until closure. of this research. In addition, a reduction of one month is expected in the total time of the project, equivalent to 4.16% of the period initially offered. These results demonstrate the effectiveness of Lean Construction in optimizing costs and times in a healthcare infrastructure project. The methodology not only allowed significant reductions in the budget, but also guaranteed effective control of project progress, resulting in compliance with planned amounts, in shorter deadlines and greater efficiency in execution.